Sunday
March 26, 2017

Post a New Question

Posted by on .

How do I simplify this? :l
4(x+y)]/(5x^2y^3) ÷ (-2x-2y)/10

  • Math - ,

    4(x+y)]/(5x^2y^3) ÷ (-2x-2y)/10 =

    10 * 4 ( x + y ) / [ ( 5 x ^ 2 y ^ 3 ) * ( - 2 x - 2 y ) ] =

    40 ( x + y ) / [ ( 5 x ^ 2 y ^ 3 ) * - 2 ( x + y ) ] =

    40 / - 2 * 5 x ^ 2 y ^ 3 ) =

    40 / - 10 ( x ^ 2 y ^ 3 ) =

    - 4 / x ^ 2 y ^ 3

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question